Surveys for development. A multidisciplinary approach. International Institute for Aerial Survey and Earth Sciences Symposium, December 1976. - (:unkn) unknown (My University, 1977)
Inhalt Veränderte Ansichten über Entwicklung - Kulturelle Aspekte der Entwicklung - Regionale Siedlungssysteme - usw.
Keywords: Entwicklung